Kontribusi Nur Ad-Din Ar-Raniri dan Abd Ar-Rauf As-Sinkili dalam Pengembangan Kajian Hadis di Indonesia - Farida, Umma (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2017)
Kedudukan hadis sebagai sumber hukum kedua setelah al-Qur’an menjadikan perhatian dan kajian terhadapnya amatlah penting. Peran Nur ad-Din ar-Raniri dan Abd ar-Rauf as-Sinkili dalam mengembangkan kajian hadis di Indonesia pada abad ke-17 H. yang pada saat itu belum populer dan belum menjadi kajian keilmuan secara mandiri tidaklah dapat dipandang sebelah mata. Artikel ini hendak melihat kontribusi yang diberikan dua ulama tersebut, dengan menggunakan pendekatan deskriptif-kualitatif. Ar-Raniri berhasil mendekatkan umat Islam Indonesia dengan hadis melalui karyanya, Hidâyat al-Hâbiîb at-Targîb wa at-Tarhîb. Demikian pula dengan as-Sinkili melalui dua karyanya, Syarh Latîf 'ala Arba'în Hadiîst al-Imam an-Nawawi dan al-Mawa'iz al-Badî'ah.The position of hadith as the second source after the Qur'an makes the study of it very important. The role of Nur ad-Din ar-Raniri and Abd ar-Rauf as-Sinkili in developing the study of hadith in Indonesia in the 17th century H. which was not popular and had not become a scientific study independently at that time can not be underestimated. This article looks at the contributions of these two scholars, using a descriptive-qualitative approach. Ar-Raniri was successfull in making Indonesian Muslims closer to the hadith through his work, Hidâyat al-Hâbiîb at-Targîb wa at-Tarhîb. Similarly, as-Sinkili through his two works, Syarh Latîf 'ala Arba'în Hadiîst an li al-Imam an-Nawawi and al-Mawa'iz al-Badî' ah.